Memorizing the Qur’an in 20 Days: Participatory Action Research in Pidie Jaya Aceh - Tiy Kusmarrabbi Karo; Teuku Raudhan Muhammad Akhyar; Bahrul Ulum (ASSUNNAH PRESS, 2022)
In the U Paneuk Village, Masjid Tuha, which take place in Meureudu Pidie Jaya, in the province of Aceh, the Youth Qur’an Memorizer that their ages is below 15 years old or still in a elementary school, on 20 days of improvisation, we have found a lot of problem in the reading and memorizing of Qur’an also a lot of problems that we found in cases of attitude in the youth qur’an memorizer, and on that cases, the team of Community Service Activities tried to form an improvement and give solution to them and that is a Qu’ran quarantine in 20 days ramadhan with 28 student participation also we partnering with SDIT An-nuur and a few teachers on the village to succeed in clearing the problem that the team faces along the way to help youth memorizer to have great Qur’an memorize and have them read less wrong and added more of Qur’an inside their hearth, in this Community Service Activities we use Participatory Action Research that gain a lot of benefit from the agenda such as metode for good quarantine or metode for strong memorize and a lot of expirience in teaching children and sosialize with village citizen